Structuring educational decisions using the multiple sorting task: An example focusing on international placements in nursing. (September 2017) - Morrison, P.; Gluyas, H.; Stomski, N.J.
Abstract: Practical examples of the steps involved in the planning and execution of the multiple sorting task are frequently lacking in published reports. This article demonstrates how the multiple sorting task can be used to structure conversations with a group of health professionals planning an international placement for nursing students. Sixteen participants were drawn from diverse professional backgrounds, including academia, clinical practice, government policy, and placement administrators. Participants sorted 17 statements written on cards into categories of their choice and noted why they sorted the cards into these particular groups. Data were analysed using multidimensional scaling and qualitative perspectives. The analysis identified four key themes that detailed the participants' views about international placements. These findings demonstrate how the multiple sorting task can be used to generate information that facilitates the examination of important facets of health care practice that universities could cover in preparing students for international placements. Highlights: The multiple sorting task facilitates shared decision-making in developing education content. Sharing priorities in a group context will lead to more cohesive teams which embrace change. The multiple sorting task can integrate qualitative and quantitative research methods.